التفكير الإيجابي وحسن الظن بالله وقضاءه وقدره في ضوء الهدي النبوي = Positive thinking and good impression towards Allah and His predestination in light of Prophetic guidance - Mat Nor, Norhayati; Mohd Marzuki, Zunaidah (Department of Usuluddin and Comparative Religion, Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University of Malaysia, 2020)
The research aims to highlight the theme of positive thinking and good faith in God and His will in light of Prophetic guidance. The research is based on inductive and analytical method through studying Hadith collection, its commentaries and other important sources which contained significant hadith on this theme, that further explain the topic and help finding of results. Six Hadith were selected; four of which relating to God, and another two to His decree. The finding brought forth important results, which includes: a close relationship between good faith and man’s worshipping of God Almighty as in the first hadith; a Muslim should think positively in all situations and events; in facing happiness and misery, ease and hardship, spacious and distress, even in facing death as in the second hadith; the third Hadith indicates good faith in God and be sure of Him in time of dying and facing the death of loved ones; as well as good faith of God is a sign of perfection and faithful worship of individual as pointed out in the fourth Hadith; the fifth hadith shows how the Prophet SAW teaches us that calamity expiates the sins and cleans hearts from impurity. The sixth Hadith indicates that among positive behaviours are patience and thankful in life, and this was required of human that characterized him in either condition when facing positive or negative cases. Muslim should put trust and good faith in the Almighty at all moments, in good and bad times with patience and thankfulness, and much more he must think well of his Lord in two cases: in the act of worship, and during calamities.